Children's emotional and behavioral response following a migration: a scoping review - Alejandra Salazar Andrade; Josefina Sala Roca; Sara Rodríguez Pérez (Elsevier, 2023)
Background: Migration is a present and pressing global phenomenon, as climate change and political instability continue to rise, more populations will be forced to relocate. Efficient strategies must be in place to aid the transition of vulnerable populations - such as children - and strategic interventions designed based on an understanding of their particular needs and risks. Aim of the review: This article reviewed recent research regarding the mental health of migrant children identifying a wide array of common characteristics to their emotional and behavioral responses following a migration, and compiled an extensive list of protective and risk factors. 48 studies were selected from Proquest, WOS, SCOPUS, and Pubpsych published between 2015 and 2022 covering studies of children around the world. Findings: The migration-related factors that most negatively impacted children's mental health were experiences such as discrimination, loss of access to governmental and educational resources, premigration trauma, loss of community, cultural distance and acculturation, the burden on the family unit, and socioeconomic difficulties. Thus, with the right interventions and policy changes, it is possible to make migration a non-traumatic experience in order to avoid the common emergence of depressive symptoms, PTSS (post-traumatic stress symptoms), anxiety, and other mental health issues. Supporting the family unit's transition, encouraging peer connections, and directing government aid to expedite resources upon arrival will serve as protective factors for children while they integrate into their new environment.